A shot number based approach to performance analysis in table tennis - Tamaki, S.; Yoshida, K.; Yamada, K. (Journal of Human Kinetics, 2017)
The current study proposes a novel approach that improves the conventional performance analysis in table tennis by introducing the concept of frequency, or the number of shots, of each shot number. The improvements over the conventional method are as follows: better accuracy of the evaluation of skills and tactics of players, additional insights into scoring and returning skills and ease of understanding the results with a single criterion. The performance analysis of matches played at the 2012 Summer Olympics in London was conducted using the proposed method. The results showed some effects of the shot number and gender differences in table tennis. Furthermore, comparisons were made between Chinese players and players from other countries, what threw light on the skills and tactics of the Chinese players. The present findings demonstrate that the proposed method provides useful information and has some advantages over the conventional method.